Offence of Theft The Case Study Of theft of medical products - Pullarp , Nannaparit (Huachiew Chalermprakiet Law Journal, 2024)
The Criminal Code, for the crime of theft has provided for several cases of aggravating circumstances such as those specified as crimes under section 335, theft of religious objects section 335 bis and other crimes section 336 bis. At present, there are many types of property some of which It is a high value asset. It is also property that can be used to treat sickness, disease or human condition, that is "medical products". If such property is stolen, it will not only affect personal safety but also affect society and the nation. This article examines the provisions for theft offenses related to medical products. It will conduct a comparative study with the provisions of United States law that specifically defines the offense of theft of medical products. The penalty is higher than general theft. To apply guidelines to suit crimes committed in Thai society. Therefore, the Criminal Code should be amended to include specific provisions regarding theft of medical products.